Impact of FDI on Human Capital in Pakistan - Mahmood, Haider; Chaudhary, A.R (Asian Journal of Empirical Research, 2012)
The study finds the impact of foreign direct investment on human capital in Pakistan. It uses foreign direct investment, economic growth rate and government expenditure on education as independent variables and human capital index as dependent variable. ADF, PP, Ng-Perron and Zivot-Andrews unit root tests are applied to find the level of integration in time series. The ARDL and its error correction model are applied to find the long run and short run relationships. The study finds the long run and short run relationships in the model. Foreign direct investment and economic growth have positive and significant impact on human capital in Pakistan.